Preschoolers' problem behavior, prosocial behavior, and language ability in a Latin-American context: The roles of child executive functions and socialization environments - Lohndorf, R. T.; Vermeer, H. J.; Carcamo, R. A.; De la Harper, C.; Mesman, J. (My University, 2019)
Child executive functions and socialization environments are crucial for the socioemotional and cognitive development of preschoolers. This study examined the role of socioeconomic status (SES), ethnicity, executive functions (EFs), quality of the home environment, quantity of maternal care, and quality and quantity of professional childcare as predictors of five-year-old preschoolers' problem behavior, prosocial behavior, and language ability in 77 low-SES families with a Chilean majority or Mapuche minority background in Chile. Executive functions and the quality of the home environment were positively associated with language ability, whereas quantity of childcare was inversely related to children's language ability. All other associations were non-significant. The results corroborate the vital roles of child executive functioning and stimulating and responsive parenting in child language ability in a Latin-American context. Furthermore, our findings revealed inadequate preschool classroom quality and provide new evidence from southern Chile of the urgent need to improve the quality of Chilean children's preprimary education as a catalyst for reducing social disparities. (C) 2019 Published by Elsevier Inc.
Keywords: parental caregiving; professional childcare; executive functions; socioemotional adjustment; language ability; chilean preschoolers